Colloid system for improving adhesive force of nano-hydroxyapatite as well as preparation method and application of colloid system

By adding fumed silica and traditional Chinese medicine extracts to a nano-hydroxyapatite dispersion, combined with a charge modifier, a thixotropic network structure is formed, solving the problem of insufficient adhesion of nano-hydroxyapatite in oral cleaning products and achieving long-lasting antibacterial and anti-inflammatory effects.

CN120899572APending Publication Date: 2025-11-07CHENGDU CHENMEIJIA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510317513.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

In existing technologies, nano-hydroxyapatite particles are easily washed away after use in thick substances such as toothpaste and gel, and cannot effectively adhere to teeth and periodontal tissues, lacking long-lasting antibacterial and anti-inflammatory effects.

Method used

By adding fumed silica powder and traditional Chinese medicine extracts to nano-hydroxyapatite dispersion and using charge modifiers such as polyquaternary ammonium salts, a thixotropic network structure is formed, which improves its suspension stability and adhesion in aqueous solution.

Benefits of technology

This technology enables long-lasting adhesion of nano-hydroxyapatite in oral cleaning products, enhancing antibacterial and anti-inflammatory effects, reducing particle loss, and improving tooth repair function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005316389860000101
    Figure BDA0005316389860000101
  • Figure BDA0005316389860000102
    Figure BDA0005316389860000102
  • Figure BDA0005316389860000111
    Figure BDA0005316389860000111
Patent Text Reader

Abstract

The invention relates to the technical field of mouth and tooth cleaning and repairing, and discloses a colloid system for improving the adhesive force of nano-hydroxyapatite and a preparation method and application of the colloid system. Preparing a solution containing a dispersing agent; adding the nano-hydroxyapatite into the solution containing the dispersing agent, and stirring to enable the nano-hydroxyapatite to be fully dispersed; adding a charge modifier into the solution; fumed silica powder is added into the solution; adding divaricate saposhnikovia root and eclipta prostrata extract into the solution, and stirring; finally, adding the colloidal solution and stirring to uniformly distribute the colloidal solution; adjusting the pH value, and filtering to obtain a mixed solution colloid system. When the tooth repairing agent is applied to enamel and periodontium, the adhesive force of nano-hydroxyapatite particles to teeth can be increased, so that the tooth repairing capability is improved. After chemical bonds on the surfaces of the particles are combined with traditional Chinese medicine components, antibacterial and blood coagulation components in the traditional Chinese medicine can be further slowly released to teeth and periodontium.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of oral cavity cleaning and repairing, in particular to a nano-hydroxyapatite colloidal system, a preparation method and application thereof. BACKGROUND

[0002] Hydroxyapatite microparticles are gradually widely recognized due to the composition thereof being close to 97% or above of the composition of human bone, especially the composition of tooth enamel, and having a remineralization effect when attached to the periodontal and tooth enamel surface. Therefore, the hydroxyapatite microparticles are generally added in toothpaste and medical gel to play a corresponding role.

[0003] The hydroxyapatite microparticles are combined with antibacterial and hemostatic traditional Chinese medicine extracts to play a mineralization role, and also to inhibit bacteria and inflammation and stop bleeding in the periodontal, thereby being more beneficial to the health of teeth. This aspect still needs to be researched and developed, especially the application after being combined with traditional Chinese medicine. Because oral bacteria exist for a long time, daily antibacterial and bleeding point control are generally required to reduce periodontal inflammation.

[0004] When the hydroxyapatite microparticles are used in thick paste (such as toothpaste, gel, and oral paste), there is a need to clean the mouth soon after use, and a large amount of hydroxyapatite microparticles are inevitably washed away after being stirred and washed by toothbrush bristles and clean water, so that the hydroxyapatite microparticles cannot be attached to the teeth and periodontal to play a mineralization role.

[0005] Therefore, it is necessary to design a colloidal system that enhances the adhesion of hydroxyapatite, loads antibacterial and hemostatic traditional Chinese medicine components, and can be used in paste and spray. SUMMARY

[0006] The present application provides a colloidal system for improving the adhesion of nano-hydroxyapatite, a preparation method and application thereof, and aims to solve the problems of lack of long-acting adhesion and antibacterial effect in current oral cavity cleaning and repairing agents.

[0007] In one aspect, the present application provides a preparation method and application of a colloidal system for improving the adhesion of nano-hydroxyapatite, which comprises the following steps:

[0008] S1: preparing a xanthan gum colloidal solution with a mass fraction of 2%, and standing after preparation for standby use;

[0009] S2: adding a dispersant to deionized water to obtain a dispersant solution for standby use;

[0010] S3: preparing an adsorption-enhanced hydroxyapatite: adding nano-hydroxyapatite powder to the dispersant solution, and continuously adding a charge modifier for hydroxyapatite to disperse the charge-modified nano-hydroxyapatite in the aqueous solution, to obtain a nano-hydroxyapatite dispersion;

[0011] S4: adding fumed silica powder into the nanometer hydroxyapatite dispersion liquid and stirring to disperse it into the solution;

[0012] S5: continuously adding the wind-preventing extract and the euphorbia extract into the nanometer hydroxyapatite dispersion liquid to obtain a traditional Chinese medicine mixed dispersion liquid;

[0013] S6: adding the xanthan gum colloid solution into the traditional Chinese medicine mixed dispersion liquid to uniformly disperse the xanthan gum into the solution, thereby obtaining a mixed colloid solution;

[0014] S7: adjusting the pH of the mixed colloid solution to 4.5-10, filtering the mixed colloid solution using a filter screen, and obtaining a nanometer hydroxyapatite colloid system;

[0015] In steps S2-S5, each time a new component is added to the original system, the stirring is performed.

[0016] Further, the dispersant is polysorbate-80, and the mass fraction of the dispersant in the solution is 0.1-0.5%.

[0017] Further, the charge modifier is a combination of one or more of polyquaternary ammonium salt, lysine salt, spermine salt, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride.

[0018] In another aspect, the present application also provides a nanometer hydroxyapatite colloid system obtained by the above preparation method.

[0019] In still another aspect, the present application also provides an application of the above nanometer hydroxyapatite colloid system, and the nanometer hydroxyapatite colloid system is used in a spray or paste for oral cleaning and tooth repair and preparation thereof.

[0020] The nanometer hydroxyapatite colloid system is prepared by the following method:

[0021] A xanthan gum colloid solution with a mass fraction of 2% is prepared, and after preparation, the solution is left to stand for standby;

[0022] A dispersant solution is obtained by adding a dispersant into deionized water for standby;

[0023] An adsorption-enhanced hydroxyapatite is prepared by adding nanometer hydroxyapatite powder into the water solution containing the dispersant, and then adding a charge modifier for hydroxyapatite, so that the nanometer hydroxyapatite after charge modification is dispersed in the water solution; the charge modifier includes a combination of one or more of polyquaternary ammonium salt, lysine salt, spermine salt, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride.

[0024] Fumed silica powder is added into the nanometer hydroxyapatite dispersion liquid, and stirring is performed to disperse it into the solution;

[0025] adding the extract of Radix Saposhnikoviae and the extract of Eclipta prostrata L. to the nanometer hydroxyapatite dispersion solution to obtain a mixed dispersion solution of traditional Chinese medicine;

[0026] adding the xanthan gum colloid solution to the mixed dispersion solution of traditional Chinese medicine to uniformly disperse the xanthan gum in the solution to obtain a mixed colloid solution;

[0027] adjusting the pH of the mixed colloid solution to 4.5-10, and filtering to obtain the colloid system.

[0028] Further, when the colloid system is used as a spray or paste for oral cleaning and tooth repair, it further comprises:

[0029] adding any one or a combination of more than one of a preservative, a flavoring agent, a thickening agent and an abrasive agent to the colloid system to obtain a spray or paste for oral cleaning and tooth repair.

[0030] Further, the spray and the paste are changed by adjusting the mass ratio of the added xanthan gum, the hydrated silicon dioxide and the nanometer hydroxyapatite.

[0031] Further, when the colloid system is used as a component of the spray, the filtering is used to remove particles with a particle size greater than 200 microns.

[0032] Further, when the colloid system is used as a component of the spray, the mass ratio of the added xanthan gum, the hydrated silicon dioxide and the nanometer hydroxyapatite is 0.00-0.5:0.5-15:0.5-20; at this time, the colloid system presents a sol system.

[0033] When the colloid system is used as a component of the paste, the mass ratio of the added xanthan gum, the hydrated silicon dioxide and the nanometer hydroxyapatite is 0.0-5:1-15:2-20; at this time, the colloid system presents a gel system.

[0034] In the present application, the fumed hydrated silicon dioxide microparticles can improve the suspension stability of hydroxyapatite in an aqueous solution, and the stability mechanism is determined based on the chemical properties of the surfaces of the silicon dioxide and the hydroxyapatite.

[0035] When the hydrated silicon dioxide microparticles are introduced into the nanometer hydroxyapatite suspension system, they play an important role in stability and rheological behavior, especially hydrogen bonding and thixotropic network formation. These mechanisms make the suspension stable when at rest, but quickly thin after slight shaking, thereby being suitable for spray applications.

[0036] Both the hydrated silicon dioxide and the nanometer hydroxyapatite contain a large number of active functional groups, so that extensive hydrogen bonding interactions can be formed between them.

[0037] The surface of hydrated silica is rich in silanol groups, which can form strong hydrogen bonds with other polar groups. The surface of nano-hydroxyapatite contains a large number of hydroxyl and phosphate groups, which can act as hydrogen bond donors or acceptors. As a result, the hydrated silica microparticles and nano-hydroxyapatite form very strong hydrogen bonds.

[0038] The main hydrogen bond interactions include: hydrogen bonds between the silanol groups of silica and the hydroxyl groups of hydroxyapatite. Hydrogen bonds are formed between the silanol groups of silica and the phosphate groups of hydroxyapatite. Water molecules act as bridges, allowing adjacent silica particles to be connected by hydrogen bonds, further enhancing the network stability of the system.

[0039] These hydrogen bond interactions promote the formation of a stable adsorption layer of hydrated silica on the surface of hydroxyapatite, thereby helping to inhibit the agglomeration and sedimentation of HAP particles.

[0040] Hydrated silica and nano-hydroxyapatite can self-assemble into a three-dimensional network structure through hydrogen bonding and van der Waals forces. This particle network has gel-like properties and can lock HAP particles in suspension, preventing sedimentation.

[0041] When left undisturbed (no shear force): hydrogen bonding is enhanced, and silica and hydroxyapatite particles form a stable network structure. The suspension exhibits a gel state, and the hydroxyapatite particles are "frozen" in the network and do not settle. Under the action of slight shaking or shear force (for example, by shaking), the network structure is destroyed, and the hydrogen bonds are partially broken, causing the suspension to become thin. The system turns into a low-viscosity liquid, making it easy to spray.

[0042] After spraying and standing (shear force removed): the network structure is re-established, and the hydroxyapatite particles are evenly distributed on the target surface and do not quickly settle. This thixotropic property makes the formulation very suitable for stabilizing large specific gravity hydroxyapatite in water suspension; it is stable during storage and flows during use, improving application convenience.

[0043] In summary, hydrated silica plays a dual role in stabilizing nano-hydroxyapatite suspension. 1) Hydrogen bonding: strong interactions between silica and hydroxyapatite prevent particle agglomeration and sedimentation. 2) Thixotropic network formation: the system remains in a gel state when left undisturbed and turns into a sprayable low-viscosity liquid after slight shaking, and the network quickly recovers after use, improving the uniform distribution of hydroxyapatite on the target surface. This stable and sprayable property makes it valuable in biomedical coatings, oral care, functional spraying, and other applications.

[0044] In this invention, during the preparation of the spray, charge modification and thixotropic network formation ensure the dispersibility and suspension stability of nano-hydroxyapatite in the suspension, allowing it to be sprayed into a mist after a slight shake.

[0045] Hydroxyapatite microparticles, which have a density of about three times that of water, about 3.1 g / cm 3 , in water, will settle at the bottom of the container. If it is to be used in a spray, the amount of thickening agent suitable for the oral environment must be controlled to be very small, otherwise it cannot be sprayed or it will be sprayed in the form of water beads or columns. To achieve a spray, the dispersibility of the hydroxyapatite microparticles needs to be improved, and the particles need to be prevented from sticking together and clogging the spray head. At the same time, the time for the particles to settle after being suspended in the liquid after gentle shaking needs to be increased, and the speed of the particles needs to be slowed down.

[0046] One of the problems that the present application aims to solve is the settling and particle aggregation of nano-hydroxyapatite particles in an aqueous solution.

[0047] By adding a positively charged compound, such as polyquaternary ammonium salt lysine, etc., to the liquid containing hydroxyapatite particles, the suspension stability of the hydroxyapatite particles in water can be greatly improved. Without or with a very small amount of thickening agent, the nano-hydroxyapatite can be suspended in the liquid in the form of a sol system for 5-10 minutes after gentle shaking, fully meeting the user's requirements for spray use.

[0048] A water-soluble positively charged compound (polyquaternary ammonium salt, lysine, arginine, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride) will be adsorbed onto the surface of the nano-hydroxyapatite particles when added to water, through the electrostatic force of the negatively charged phosphorus on the surface of the apatite particles. As a result, the surface of the hydroxyapatite is covered with a large number of positive charges, and the zeta potential is greatly improved. Through the mutual repulsion of the same charges, this zeta potential is sufficient to overcome the gravitational force of a portion of the nano-sized apatite particles, allowing the hydroxyapatite particles to be suspended in water and not to settle at the bottom or to aggregate with each other. The viscosity of this colloidal system is very low, and it can be used as a spray. At the same time, this charge modification of the hydroxyapatite significantly improves its adhesion to teeth and enhances its repair function on teeth.

[0049] Of course, the increase in the zeta potential of the surface of the hydroxyapatite can also be achieved by lowering the pH of the aqueous solution, but the required pH is much lower than the minimum requirement for mouthwash or oral spray, which will irritate the oral cavity and erode the teeth, and will not achieve the purpose of dental health. Therefore, it is not feasible to simply use the lowering of the pH of the liquid to improve the suspension of the hydroxyapatite.

[0050] In addition, chitosan can bind to hydroxyapatite, which has been extensively studied and has many applications. However, experiments have found that pure chitosan (including chitooligosaccharide) does not play a role in the stability of hydroxyapatite suspension in aqueous solution, even if the pH of the solution is adjusted to 5.5. In theory, at a lower pH, the amino groups on chitosan will be positively charged, and if they can bind to hydroxyapatite, they will increase the repulsive force between hydroxyapatite particles, increasing stability. However, when experiments were conducted to detect the adhesion of chitosan to hydroxyapatite, the experimental results showed that the mutual repulsive force generated by chitosan was not enough to overcome the gravity of hydroxyapatite. It may be that chitosan (not modified chitosan quaternary ammonium salt) is difficult to bind firmly to hydroxyapatite in aqueous solution, or it may be that the positive charge density of chitosan is not sufficient under the pH conditions required for oral products.

[0051] In some cases, even with the addition of positively charged compounds, some hydroxyapatite particles will still settle to the bottom, because of the distribution of hydroxyapatite particle size, there will always be some larger particles that overcome the mutual repulsive force caused by zeta potential. Surprisingly, experiments have found that in this case, the addition of a small amount of negatively charged high molecular weight compounds such as xanthan gum can form a loose network structure in the solution. This loose network structure can prevent hydroxyapatite particles from forming a dense layer of clumps at the bottom of the container. With a slight shake, this loose material will quickly re-disperse into the solution.

[0052] The composition of hydroxyapatite contains a large amount of calcium and phosphate, so its particle surface is simultaneously positively and negatively charged. Due to this property, a hydroxyapatite particle can physically interact with a variety of negatively charged polymers (such as xanthan gum) and positively charged polymers (such as polyquaternary ammonium salt, lysine, spermine, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride, etc.). This interaction forms a loose network structure in which nano-hydroxyapatite particles are wrapped. Unlike hard clumps, this loose network does not harden at the bottom of the container. The force between them is a physical force, which is very weak and can be easily broken by a slight shake. The hydroxyapatite particles are re-released into the solution by physical force with positively and negatively charged high molecular weight compounds (such as xanthan gum, polyquaternary ammonium salt, lysine, etc.), without affecting use.

[0053] Aerosol hydrophobic silica can form a loose network structure with hydroxyapatite particles in a solution containing hydroxyapatite. This loose network structure has strong thixotropic rheological properties, which can help hydroxyapatite particles to be stably suspended in the solution system without affecting the use as a spray.

[0054] Hydrated silica as thickening agent and abrasive agent in toothpaste, although widely used in paste, including the paste containing hydroxyapatite, but used in thixotropic sol system, research and application is less, especially when used with several other ingredients in the invention. About the use of hydrated silica to form a thixotropic network structure to stabilize the suspension stability of hydroxyapatite in solution, which will be further described in the examples.

[0055] It should be noted that the thixotropic properties of the above-mentioned colloidal refers to adjusting the proportion of auxiliary ingredients without changing the use of active ingredients to change the colloidal system between sol and gel.

[0056] Compared with the prior art, the present application has the following advantages:

[0057] Due to the charge adjustment of the positively charged ions and the like to the hydroxyapatite particles, the surface of the particles has more positive charges. When the particles are applied to the enamel and periodontal by spraying, the enamel and periodontal are negatively charged, so that the adhesion between them is increased by the attraction of positive and negative charges.

[0058] The modification of hydroxyapatite with positive reagents improves its suspension stability in the spray, which is crucial for maintaining the effect of hydroxyapatite.

[0059] At the same time, the formation of a thixotropic network structure by hydrated silica further ensures the suspension stability of hydroxyapatite.

[0060] In addition, due to the presence of many chemical bonds on the surface of the hydroxyapatite particles, when combined with the extracts of traditional Chinese medicine such as wind-preventing and drought-resistant lotus, they can load the efficacy factors for a long time. When used as a spray or paste on teeth and gums, due to the weight adhesion and charge adhesion of hydroxyapatite, the traditional Chinese medicine ingredients can be released for a long time in the corresponding parts, and the loss of the traditional Chinese medicine ingredients can be avoided when rinsing (paste use) or swallowing and spitting out (spray use), so that the corresponding effect cannot be achieved.

[0061] When used as a spray, the loss of nanometer hydroxyapatite is further reduced because it does not need to be rinsed immediately. When used for spray preparation, the content of thickening agent and abrasive agent needs to be reduced; when used for paste preparation, the content of thickening agent and abrasive agent needs to be increased. DETAILED DESCRIPTION

[0062] The technical solutions in the embodiments of the present application will be described below. Obviously, the described embodiments are only a part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0063] Example 1

[0064] Test Examples 1-15 were prepared according to the following preparation procedure and weight ratio, and the ingredient usage table is shown in Table 1.1 and Table 1.2.

[0065] The following are the general steps for sample preparation:

[0066] 1. Add a certain amount of deionized water to a container at room temperature, then add the dispersant polysorbate-80 to the water and stir evenly at 200-300 rpm.

[0067] 2. Gradually add nano-hydroxyapatite powder to the solution containing the dispersant under high-speed stirring (500-800 rpm). Continue stirring for 10 to 30 minutes to evenly disperse the added hydroxyapatite particles in the aqueous solution.

[0068] Add the required charge modifier to the solution and stir at 200-300 rpm for 2-3 minutes to completely dissolve it.

[0069] 3. Add hydrated silica microparticle powder to the above solution, disperse evenly at 200-300 rpm and stir for 2-3 minutes to hydrate it.

[0070] 5. Add traditional Chinese medicine extract to the above solution and continue stirring (200-300 rpm) to completely dissolve it.

[0071] 6. Add other auxiliary ingredients (flavorings, preservatives, etc.) under stirring (200-300 rpm).

[0072] 7. Finally, filter the solution (300 mesh filter) to ensure that no particles clog the nozzle. Filter out possible larger particles.

[0073] Among them, the traditional Chinese medicine extract is preferably the extract of Saposhnikovia divaricata and the extract of Eclipta prostrata, and the extract of Saposhnikovia divaricata is obtained by the following method:

[0074] Raw material processing: first, grind the dried roots of Saposhnikovia divaricata into powder.

[0075] Solvent extraction: mix the powder with an appropriate amount of solvent (such as water, ethanol or acetone, etc.) for soaking or reflux extraction. Use 70% to 95% ethanol or aqueous solution for extraction.

[0076] Concentration and drying: the extracted solution is concentrated to remove the solvent, and then spray drying, vacuum drying, etc. to obtain the extract of Saposhnikovia divaricata.

[0077] The extract of Eclipta prostrata is obtained by the following method:

[0078] Raw material processing: dry the whole plant of Euphorbia humifusa or leaves, and then crush them into powder.

[0079] Solvent extraction: use water, ethanol or 70% ethanol solution as solvent to carry out conventional soaking or reflux extraction. The soaking time is several hours to one day, and the reflux extraction can improve the extraction efficiency. The common reflux time is 2-3 hours.

[0080] Concentration and drying: the extract is concentrated to remove excess solvent. Then the solvent is removed by freeze-drying, spray-drying or other methods to obtain Euphorbia humifusa extract.

[0081] Table 1.1 Spray formulation containing hydroxyapatite

[0082]

[0083] Table 1.2

[0084]

[0085]

[0086] It should be noted that in Test Example 1, the hydroxyapatite particles quickly sink to the bottom. After standing for 24 hours, the hydroxyapatite that sinks to the bottom will clump and be difficult to re-disperse into the solution by shaking.

[0087] In Test Examples 3 and 4, the liquid viscosity is low, which is suitable for spraying. Most of the hydroxyapatite is suspended in the solution to form a translucent sol, and after standing for 24 hours, part of it still sinks to the bottom and is difficult to re-disperse into the solution by shaking.

[0088] In Test Examples 5-15, the hydroxyapatite is suspended in the solution to form a translucent sol, and the viscosity is very low, which is suitable for spraying. After standing for 24 hours, loose structures appear at the bottom, which are quickly dispersed and evenly dispersed into the solution by shaking the container. The whole liquid is a translucent sol, which is suitable for spraying.

[0089] The pH of Test Examples 1-15 is neutral, which is suitable for oral use.

[0090] Hydrated silicon dioxide is used as a thickening agent and abrasive in toothpaste. Although it is widely used in paste, it is also used in paste containing hydroxyapatite, but it is rarely used in thixotropic sol systems, especially when used with other ingredients in this invention. It should be noted that the thixotropic properties of the above-mentioned colloids refer to adjusting the proportion of auxiliary ingredients without changing the use properties of active ingredients to change the colloidal system between sol and gel.

[0091] Example 2

[0092] The following table (Tables 2.1-2.3) lists several examples of spray formulations containing hydroxyapatite. Silica microparticles are used to improve the suspension stability of hydroxyapatite in aqueous solutions.

[0093] Table 2.1 Spray formulations containing hydroxyapatite

[0094]

[0095]

[0096] Table 2.2

[0097]

[0098]

[0099] Table 2.3

[0100]

[0101]

[0102] The samples in the above test examples formed a loose network structure when left to stand. During use, a gentle shaking will break down this network structure, resulting in a uniform, low-viscosity liquid that is very easy to spray.

[0103] The modifications to hydroxyapatite listed above can be clearly demonstrated by measuring the zeta potential of its solution. The following table (see Table 3) lists the zeta potentials of some of the test samples in Tables 1.1, 1.2, and 2.1-2.3.

[0104] Table 3. Zeta potential values ​​of the samples

[0105] Test Example No. 1 4 24 28 29 31 32 ζ-potential (mv) 1 -32.0 2 -32.0 3 - -11 +78 +45 +16 +12 +8 +19

[0106] As shown in the table above, the addition of the chemical substances can increase the zeta potential of hydroxyapatite-containing liquids. This indicates that the addition of these substances can significantly improve the surface charge characteristics of hydroxyapatite, changing it from negative to positive, and thus enhancing the adsorption performance of hydroxyapatite on teeth.

[0107] The properties of the solution are detected based on rheological testing:

[0108] Rheological testing can reveal whether a solution forms a network structure under static (storage) conditions and its flow behavior, thus revealing viscosity changes in the solution under static conditions and after oscillation (shear or shaking). This helps to assess internal structural characteristics, thixotropy, and shear-dependent viscosity changes, which is crucial for understanding formulation stability and application performance.

[0109] Two rheological tests were performed on the solution to determine the rheological properties: frequency sweep and flow behavior tests. The frequency sweep test was used to determine whether a network structure existed in the solution, while the flow behavior test was used to evaluate the change in viscosity of the solution under storage (static) and oscillation (dynamic) conditions and whether the network structure within the solution was thixotropic.

[0110] The results of the rheological tests on the sample of Test Example 22 are shown in Table 4.

[0111] Table 4. Results of the frequency sweep test

[0112]

[0113] The data show that when the frequency is low, the viscous modulus (G") is greater than the storage modulus (G'), but as the frequency increases, the viscous modulus gradually decreases and becomes less than the storage modulus, indicating that a weak network structure exists in the system. This weak network structure is exactly what is needed for the system. This network structure not only ensures that the hydroxyapatite particles do not settle to the bottom of the container, thereby forming aggregates and even clumps, but it is also the solution system in which the hydroxyapatite can be easily suspended under slight shaking, becoming an easily sprayable viscous sol system.

[0114] The same sample, when no fumed silica microparticles are added, the hydroxyapatite nanoparticles quickly settle to the bottom of the container, indicating that the addition of fumed silica microparticles is crucial for the stabilization of hydroxyapatite. The above results show that the fumed silica achieves the stability of the system by forming a network structure in the system.

[0115] The following are the results of the rheological behavior of the sample of Test Example 22:

[0116] Table 5. Results of the flow behavior test on sample 22

[0117]

[0118]

[0119] The flow behavior clearly shows that when the solution is in a static state (low shear rate or under storage conditions), the sample viscosity is very high, reaching more than 130 Pa-s. This high viscosity helps to maintain the storage stability of the system, effectively preventing the settlement of hydroxyapatite.

[0120] On the other hand, when the shear strain rate is increased, the viscosity of the sample decreases rapidly, indicating that the internal network is destroyed under the action of shear. When the shear rate is increased to the extent comparable to manual shaking, the viscosity of the solution is reduced to a very low level (0.08 Pa·s), indicating that the internal network structure is destroyed by shaking and the like, and the solution has very low viscosity, so that the solution becomes completely sprayable.

[0121] The rheological mechanics measurement clearly shows that the formed sample has a thixotropic network structure, ensuring the storage stability of the sample; at the same time, when the sample is used, the viscosity of the solution can be reduced to a very low level by appropriate shaking, so that the spraying operation can be realized.

[0122] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, but not to limit it, although the present application has been described in detail with reference to the above examples, those skilled in the art should understand that: the specific embodiments of the present application can still be modified or replaced by the equivalent, without departing from the spirit and scope of the present application, any modification or equivalent replacement, which should be covered within the protection scope of the claims of the present application.

Claims

1. A method for preparing a colloidal system for improving the adhesion of nanohydroxyapatite, characterized by, It comprises the following steps: S1: prepare a xanthan gum colloid solution with a mass fraction of 2%, and stand after preparation; S2: add a dispersant to deionized water to obtain a dispersant solution for standby; S3: prepare adsorption-enhanced hydroxyapatite: add nano-hydroxyapatite powder to the dispersant solution, and then add a charge modifier for hydroxyapatite, so that the charge-modified nano-hydroxyapatite is dispersed in the aqueous solution, thereby obtaining a nano-hydroxyapatite dispersion liquid; S4: add fumed silica powder to the nano-hydroxyapatite dispersion liquid and stir to disperse it in the solution; S5: continue to add the extract of Poria cocos and the extract of Eclipta prostrata to the nano-hydroxyapatite dispersion liquid to obtain a traditional Chinese medicine mixed dispersion liquid; S6: add the xanthan gum colloid solution to the traditional Chinese medicine mixed dispersion liquid to uniformly disperse the xanthan gum in the solution, thereby obtaining a mixed colloid solution; S7: adjust the pH of the mixed colloid solution to 4.5-10, filter the mixed colloid solution using a filter screen, and obtain a nano-hydroxyapatite colloid system. In steps S2-S5, each time a new component is added to the original system, it is added under stirring.

2. The method for preparing a nanohydroxyapatite colloid system according to claim 1, characterized in that, The dispersant is polysorbate-80, and the mass fraction of the dispersant in the solution is 0.1-0.5%.

3. The method of claim 1, wherein the nanohydroxyapatite colloidal system is prepared by the steps of: The charge modifier is a combination of one or more of polyquaternary ammonium salt, lysine salt, spermine salt, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride.

4. A nano-hydroxyapatite colloid system obtained by the preparation method of any one of claims 1-3.

5. Use of the nanohydroxyapatite colloid system according to claim 4, characterized in that, The nano-hydroxyapatite colloid system is used for preparing a spray or paste for oral cleaning and tooth repair. The nano-hydroxyapatite colloid system is prepared by the following method: Prepare a xanthan gum colloid solution with a mass fraction of 2%, and stand after preparation; Add a dispersant to deionized water to obtain a dispersant solution for standby; Prepare adsorption-enhanced hydroxyapatite: add nano-hydroxyapatite powder to the dispersant-containing aqueous solution, and then add a charge modifier for hydroxyapatite, so that the charge-modified nano-hydroxyapatite is dispersed in the aqueous solution; the charge modifier comprises a combination of one or more of polyquaternary ammonium salt, lysine salt, spermine salt, chitosan quaternary ammonium salt, choline chloride, and benzalkonium chloride; Add fumed silica powder to the nano-hydroxyapatite dispersion liquid and stir to disperse it in the solution; Add the extract of Poria cocos and the extract of Eclipta prostrata to the nano-hydroxyapatite dispersion liquid to obtain a traditional Chinese medicine mixed dispersion liquid; Add the xanthan gum colloid solution to the traditional Chinese medicine mixed dispersion liquid to uniformly disperse the xanthan gum in the solution, thereby obtaining a mixed colloid solution; Adjust the pH of the mixed colloid solution to 4.5-10, and filter to obtain the colloid system.

6. Use of a nanohydroxyapatite colloidal system according to claim 5, characterized in that, When the colloid system is used for preparing a spray or paste for oral cleaning and tooth repair, it further comprises: Add any one or more of a combination of a preservative, a flavoring agent, a thickening agent, and an abrasive to the colloid system to obtain a spray or paste for oral cleaning and tooth repair.

7. Use of a nanohydroxyapatite colloidal system according to claim 6, characterized in that, The addition mass ratio of xanthan gum, hydrated silica, and nano-hydroxyapatite is adjusted to change the spray and paste.

8. Use of a nanohydroxyapatite colloidal system according to claim 7, characterized in that, When the colloid system is used as a component of a spray, the filtration is used to remove particles with a size greater than 200 microns.

9. Use of a nanohydroxyapatite colloidal system according to claim 8, characterized in that, When the colloid system is used as a component of a spray, the mass ratio of xanthan gum, hydrated silicon dioxide and nano-hydroxyapatite is 0.00-0.5:0.5-15:0.5-20; at this time, the colloid system is in a sol system; When the colloid system is used as a component of a paste, the mass ratio of xanthan gum, hydrated silicon dioxide and nano-hydroxyapatite is 0.0-5:1-15:2-20; at this time, the colloid system is in a gel system.